Reaction pathway and kinetic study of 4,5-dihydroxyimidazolidine-2-thione synthesis by HPLC and NMR - Kalichkina, Liudmila E.; Novikov, Dmitry; Kotelnikov, Oleg A.; Malkov, Victor S.; Knyazev, Alexey S. 1978- (Heterocycles)
Process of 4,5-dihydroxyimidazolidine-2-thione (DHIT) synthesis from thiourea and glyoxal is studied. Formation of imidazole-2-thiones and 4,5-dihydroxyimidazolidin-2-one as byproducts is confirmed by NMR. The kinetics of the scalable DHIT synthesis process is studied by HPLC, and the kinetic parameters of the model based on the proposed reaction scheme are calculated. The model correctly describes the kinetics of the DHIT formation and thiourea consumption.